Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Kelas VIII SMP Negeri 1 Nunukan Selatan - Tri Wahyuni; Alimin Alimin; Asri Asri; Ramlawati Ramlawati (Universitas Negeri Makassar, 2024)
This study aims to improve student learning outcomes in participating in science learning in class VIII of SMP Negeri 1 Nunukan Selatan. This study uses a Problem Based Learning learning model and is carried out in 3 cycles. Data collection techniques were carried out with tests and non-tests, with data collection tools in the form of student activity observation sheets and final test sheets for each cycle. The procedures for implementing this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The technique of observing student activity sheets showed that there was an increase in student learning outcomes from cycle I to cycle II and from cycle II to cycle III. The percentage of complete learning outcomes in the first cycle is 67%. Cycle II to 75% and cycle III to 85%. The results of the research above prove that the Problem Based Learning learning model can improve science learning outcomes for class VIII students of SMP Negeri 1 Nunukan Selatan.